Free vibration analysis of isotropic rectangular plates on Winkler foundation using differential transform method - Kumar, Yajuvindra (Zielona Góra: Uniwersytet Zielonogórski)
A differential transform method (DTM) is used to analyze free transverse vibrations of isotropic rectangular plates resting on a Winkler foundation. Two opposite edges of the plates are assumed to be simply supported. This semi-numerical-analytical technique converts the governing differential equation and boundary conditions into algebraic equations. Characteristic equations are obtained for three combinations of clamped, simply supported and free edge conditions on the other two edges, keeping one of them to be simply supported. Numerical results show the robustness and fast convergence of the method. Correctness of the results is shown by comparing with those obtained using other methods.
Keywords: differential transform method; isotropic; rectangular; Winkler foundation